The loyalty of the literary reviser: Author, source text, target text or reader? - Feinauer, Ilse; Lourens, Amanda (Stellenbosch Papers in Linguistics Plus, 2017)
The processes of revision and translation, according to Mossop (2010:112-113), can address the problem of conflicting interests, goals and needs by taking different approaches. Translation, he suggests, should seek to achieve a balance between loyalty to the source text author and to the target text readers, whereas revision should serve the interests of the future readers of the text. As a result, revising activities will steer away from a linguistic or a text-based approach in order to prioritise the needs of the reader. The question, however, is whether revisers in literary translation processes do follow the suggested approach and prioritise the needs of the target readers. An empirical analysis of the metatextual discourse among the agents involved in three different literary translation processes seeks to answer this question. During the course of this analysis, a second question presents itself, namely whether self-revision and other-revision (Mossop 2010:167, 174) should be discerned as two distinct types of revision or whether this distinction could be refined. The results of the subsequent analysis give rise to the presumption that such a binary projection of the act of revision can be contested. It is instead suggested that revision can be plotted on a continuum, with self-revision by the translator as the one end and revision by others as the other end. The analysis of three Afrikaans novels translated into English by the same award-winning translator suggests that self-revision by the translator may find itself moving away from true self-revision (a process that is not influenced by feedback from agents other than the translator) initially to a second phase of self-revision that is shaped by revision by others (e.g. the author, reviser and editor).